STRATEGI PANITIA PENGAWAS PEMILIHAN UMUM KECAMATAN BUNGURSARI KOTA TASIKMALAYA DALAM PENCEGAHAN PELANGGARAN PEMILU 2024 PERSPEKTIF SIYASAH DUSTURIYAH: ( Studi Kasus di PANWASLU Kecamatan Bungursari) - Ecep Nurjamal; Solis Setiawati; Asep Arsyrul Munir (Program Studi Hukum Tata Negara, 2024)
General elections, hereinafter referred to as elections, are a means of popular sovereignty to elect a leader to lead a country. The elections to be held in 2024 are legislative and executive elections which will be held simultaneously. Namely, electing the President and Vice President, Members of the People's Legislative Assembly, Members of the Regional Representative Council, and Members of the Provincial and Regency/City Regional People's Representative Councils. In the stages of the general election, it is necessary to have supervision in order to minimize violations in the election. The role of oversight institutions such as PANWASLU at the sub-district level is very helpful in overseeing the stages of the election process. For this reason, it is necessary to have a strategy prepared so that the stages can run according to applicable regulations. Oversight institutions are not only to supervise but also support the stages in the election. This research was conducted to find out how the strategy carried out by PANWASLU in Bungursari District in preventing election violations as well as how election violations are in the Dusturiyah Perspective. Methodology This research uses qualitative methods. The data sources used are primary and secondary data. The results of this study are that the PANWASLU of Bungursari District has carried out several strategies to carry out prevention in elections However, after researching and conducting interviews in Bungursari District in the 2019 election, there was a violation committed, namely Money Politics. In the process of the 2024 election stages in Bungursari District, violations were also found by Pantarlih members, namely in the co-checking process but improvements had been made so that the co-coking stages were as expected. Everything that can interfere with the benefit of mankind is contrary to God's will. So election violations in the perspective of Siyasah Dusturiyah are considered to be able to interfere with the benefit of the people because in the process of selecting a leader there are several things that need attention.